BOOK REVIEWS: Copy Proof: a New Method for Design Education. (2002) - Lloyd, Peter
Copy Proof: A New Method for Design Education by: Edith Gruson and Gert Staal (Eds.) Published 2000 240pp ISBN: 90-6450-398-2